Meningkatkan Pemahaman Peserta Didik Berbantu Media Powerpoint Melalui Zoom Kelas 5 SD Negeri Tlogorejo 2 Guntur Demak 2020-2021 - Dewi Ratnawati (Universitas PGRI Semarang, 2020)
This research was motivated by the lack of understanding of students during online learning. The purpose of this study was to improve the understanding of students in grade 5 SD Negeri Tlogorejo 2 Guntur Demak through zoom assisted by powerpoint media. This research was conducted in November 2020, at SD Negeri Tlogorejo 2 Guntur Demak. This type of research is a Classroom Action Research with three cycles consisting of one meeting in one cycle. Each cycle consists of planning, implementing, observing and reflecting. Data collection techniques and tools in this study used descriptive analysis techniques for data in the form of documents of students' work, lists of values and observation sheets. The results showed that assisted by powerpoint media through zooming the learning outcomes of students increased, namely in the first cycle there were 3 students who achieved mastery learning or 30%. In the second cycle there was an increase to 7 students who completed or 70%. Whereas in cycle III there were 8 students completing or 80% an increase of 50%. From the learning results of these students, it can be concluded that through zoom assisted by powerpoint can improve students' understanding.Keywords: understanding, powerpoint, PTK